THE SOCIO-PHILOSOPHICAL SIGNIFICANCE OF THE JAPANESE TEA CEREMONY - Mirsoliyeva Nargiza (Journals Park Publishing, 2026)
The article analyzes the origin, socio-philosophical features and the role in society of the “Tea Ceremony”, one of the oldest cultural traditions of Japan. The study examines the tea ceremony not only as a national tradition and aesthetic phenomenon, but also as a cultural institution that develops social communication in society and strengthens spiritual and moral values. The social approach to the tea ceremony highlights the role of the ceremony in forming social relations, etiquette and unity, while the philosophical analysis explains the philosophy of “Wa”, “Kei”, “Sei”, “Jaku” in it. The Japanese tea ceremony, the objects and actions used in it, are also considered as cultural symbols. The article helps to understand the role of the tea ceremony in the social life and values of the Japanese people.
Keywords: Tea ceremony, “tyado